Dr Jorge Morales' contributions to the French expeditions in the Cainozoic of Africa (Kenya, Uganda, Namibia). (3rd August 2022) - Senut, Brigitte; Pickford, Martin; Gommery, Dominique; Mocke, Helke; Musalizi, Sarah
ABSTRACT: This article aims to show the interest of the work of Dr Jorge Morales on the understanding of African Ferae and Ruminantia collected in Uganda, Kenya and Namibia within the framework of collaboration with our team. This is not a revision of the systematics of these groups which is beyond the scope of the paper. Eighty taxa of Ferae are identified in the Cainozoic strata, of which thirty-nine are new. Seventeen ruminant taxa are recognised in the same deposits, of which eight are new.